Δ-MnO2 with an ultrahigh Mn4+ fraction is highly active and stable for catalytic wet air oxidation of phenol under mild conditions. Issue 15 (5th July 2017) - Ma, Changjian; Wen, Yaoyao; Rong, Chengli; Zhang, Nuowei; Zheng, Jinbao; Chen, Bing H.
Abstract : The self-reactivated δ-MnO2 catalyst was developed, and showed high activity and stability for the CWAO of phenol at a very low temperature. Abstract : δ-MnO2 with a very high amount of Mn 4+ showed high catalytic activity and stability for the catalytic wet air oxidation (CWAO) of phenol at a very low temperature of 70 °C. The abundance of Mn 4+ and reactive surface oxygen species in this catalyst, its resistance to Mn leaching, and its repeatable Mn 4+ /Mn 3+ (Mn 4+ /Mn 2+ ) redox cycles contributed greatly to its remarkable catalytic performance.